Emodin and Aloe-Emodin Suppress Breast Cancer Cell Proliferation through ERα Inhibition. (24th June 2013) - Huang, Pao-Hsuan; Huang, Chih-Yang; Chen, Mei-Chih; Lee, Yueh-Tsung; Yue, Chia-Herng; Wang, Hsin-Yi; Lin, Ho
Abstract : The anthraquinones emodin and aloe-emodin are abundant in rhubarb. Several lines of evidence indicate that emodin and aloe-emodin have estrogenic activity as phytoestrogens. However, their effects on estrogen receptor α (ER α ) activation and breast cancer cell growth remain controversial. The goal of this study is to investigate the effects and molecular mechanisms of emodin and aloe-emodin on breast cancer cell proliferation. Our results indicate that both emodin and aloe-emodin are capable of inhibiting breast cancer cell proliferation by downregulating ER α protein levels, thereby suppressing ER α transcriptional activation. Furthermore, aloe-emodin treatment led to the dissociation of heat shock protein 90 (HSP90) and ER α and increased ER α ubiquitination. Although emodin had similar effects to aloe-emodin, it was not capable of promoting HSP90/ER α dissociation and ER α ubiquitination. Protein fractionation results suggest that aloe-emodin tended to induce cytosolic ER α degradation. Although emodin might induce cytosolic ER α degradation, it primarily affected nuclear ER α distribution similar to the action of estrogen when protein degradation was blocked. In conclusion, our data demonstrate that emodin and aloe-emodin specifically suppress breast cancer cell proliferation by targeting ER α protein stability through distinct mechanisms. These findings suggest a possible application of anthraquinones in preventing or treating breast cancer in the future.